Three new species of the apterous Carventinae genus Vietnamaptera (Hemiptera: Heteroptera: Aradidae) from China - Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2011)
The monotypic genus Vietnamaptera Zhang et al. 2010 was erected for the conspicuous apterous Carventinae species V. bogiessa from Vietnam. Aradid collections from Yunnan Province in China contained three new species belonging to this genus, which are described and figured. A key to the four species is given and photos of the hitherto unknown male of Signocoris kaszabi Hoberlandt 1958 are presented.